Mesenchymal stem cells play an important role in host protective immune responses against malaria by modulating regulatory T cells. Issue 8 (12th June 2013) - Thakur, Reva S.; Tousif, Sultan; Awasthi, Vikky; Sanyal, Anirban; Atul, P. K.; Punia, Parveen; Das, Jyoti
<x xml:space="preserve">Abstract</x> Plasmodium spp. parasites, the causative agents of malaria, survive and replicate in human hosts by modulating host protective immune responses. In a rodent model, malaria manifests as a severe splenomegaly, with infiltration of cells and lympho‐proliferation as major contributing factors of the immunopathology. However, the cellular contents and the functions of these cells have not been well studied. Here, we report that Plasmodium berghei infection of mice leads to massive recruitment of mesen‐chymal stem cells (MSCs) in secondary lymphoid organs. Infusion of these cells into naïve mice was able to confer host resistance against malaria. Furthermore, MSCs augmented interleukin (IL)‐12 production but suppressed IL‐10 production in recipient animals. In addition, we observed dramatic reductions of regulatory T (Treg) cells in animals that received MSCs. Taken together, our findings have identified recruitment of MSCs as a novel host protective mechanism adopted by the host to combat malaria by modulating Treg‐cell responses.